Cognitive Functions Impact on Self-Reflection of Patients with Schizophrenia - Ter-Stepanyan, Anahit (ՀՀ ԳԱԱ)
The article represents the results of the study of cognitive functions with the help of Repeatable Battery for the Assessment of Neuropsychological Status (RBANS; Randolph, 1998), with extensive normative data capable of distinguishing between different cognitive domains such as Immediate and Delayed Memory, Visuospatial/Constructional, Attention, Language. Հոդվածում ներկայացված են ճանաչողական գործառույթների ուսումնասիրության արդյունքները՝ Նյարդահոգեբանական կարգավիճակի գնահատման կրկնվող թեստի օգնությամբ (RBANS; Randolph, 1998), որն ունի ընդարձակ նորմատիվային տվյալներ, և որի միջոցով հնարավոր է ուսումնասիրել ճանաչողական այնպիսի գործընթացներ, ինչպիսիք են անմիջական և հետաձգված հիշողությունը, տեսա-տարածական ընկալումը, ուշադրությունը, լեզվական ճկունությունը: В статье представлены результаты исследования когнитивных функций с помощью RBANS методики (RBANS; Randolph, 1998), с обширными нормативными данными, позволяющими различать различные когнитивные области, такие как непосредственная и долговременная память, визуально-пространственное восприятие, внимание, речь.
Keywords: Psychology; Neuropsychiatry